El Otro Encuentro: Gigi Otalvaro-Hormillosa's "Neo-Queer Precolonial Imagining" - Velasco, Gina (Review of Women's Studies; Vol 17 No 1-2 (2007): Review of Women's Studies Volume XVII, Numbers 1-2 (January-December 2007), 2023)
This essay examines the performance and video art piece Cosmic Blood, by Gigi Otalvaro-Hormillosa, a queer Colombian and Filipina American artist based in the San Francisco Bay Area. It argues that Cosmic Blood is a performative intervention into dominant modes of reading the racialized and gendered Filipina body, as well as a critique of absolutist notions of national and ethnic belonging. Cosmic Blood challenges the inherent heteronormativity and masculinism of dominant notions of nation and kinship, accomplishing this imaginative intervention by its retroping of the past through a lens of queer desire. Within Otalvaro-Hormillosa's retelling of the moment of first contact, queer bodily desire is the locus of power relations between colonizer and colonized. In this vision of the past, the figure of the Filipina is presented as a desiring subject, resisting the overdetermined tropes of woman as nation, territory, and land that are both a legacy of colonization, and a persistent narrative within contemporary articulations of national and diasporic belonging. In doing so, Cosmic Blood presents a possibility for forms of belonging that exceed the absolutism of race, ethnicity, and nation, while also imagining a utopian vision of the future that critiques the material conditions of the present.